Effect of water hardness on growth and survival of fry of angelfish, Pterophyllum scalare (Lichtenstein, 1823) - Vartak, V R; Bhatkar, V R; Bondre, R D; Balsare, S G (Indian Journal of Fisheries, 2011)
An experiment was conducted to study the effect of different levels of water hardness on survival and growth of two size groups (group A: 2.00 ± 0.20 cm and group B: 2.50 ± 0.20 cm) of fry of angelfish (Pterophyllum scalare). The gain in length was 1.9 ± 0.02 cm and 3.20 ± 0.04 cm in group A and B respectively in 100 mg l-1 CaCO3 hardness, which was superior among all the treatments. Survival was 100% in all treatments, but specific growth rate differed significantly within both the groups. The specific growth rate was 1.87 ± 0.07 and 2.81 ± 0.33 in group A and B, respectively in 100 mg l-1 CaCO3 hardness, which was significantly (P<0.05) higher than in other treatments. Growth rates at 50 and 100 mg l-1 CaCO3 hardness levels were not significantly different (P>0.05) in both the size groups. Among treatments, the best growth results were obtained at 100 mg l-1 CaCO3 hardness. Growth was significantly suppressed at 200 and 300 mg l-1 CaCO3 hardness in both the size groups. The results indicated that 100 mg l-1 CaCO3 is the optimum level for growth and survival of angelfish fry.